Simulation of impact assessment of crown forest fires on boundary layer of atmosphere using software PHOENICS; Proceedings of SPIE; Vol. 9680 : Atmospheric and Ocean Optics: Atmospheric Physics - Soprunenko E. Е. Elina Evgenievna; Perminov V. A. Valery Afanasievich; Reino V. V. Vladimir; Loboda E. L. Egor (Atmospheric Physics And Climate, 2015)
Title screen